The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/jbt.22275
|View full text |Cite
|
Sign up to set email alerts
|

MMP‐2 and MMP‐9 as prognostic markers for the early detection of urinary bladder cancer

Abstract: The present study assessed protein and gene expression levels of tissue inhibitor of metalloproteinase‐2 (TIMP‐2), matrix metalloproteinase‐2 (MMP‐2), and MMP‐9 in urine and blood samples of 50 patients with bladder carcinoma. The expression of TIMP‐2, MMP‐2, and MMP‐9 levels with tumor stage and grade was also assessed. Results showed that the expression levels of MMP‐2 and MMP‐9 in both blood and urine were significantly elevated in group 1 when compared with groups 2 and 3 healthy subjects. The discriminato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…MMP9, a member of the matrix metalloproteinase gene family, could be expressed to dissolve the extracellular matrix components. Fouad et al [15] revealed that MMP-9 was significantly up-regulated in both blood and urine of BCa patients and was of great discriminatory ability in the diagnosis of BCa. Wong et al [16] also demonstrated that MMP9 was a potential therapeutic target and prognostic biomarker that contribute to the progression of BCa.…”
Section: Discussionmentioning
confidence: 99%
“…MMP9, a member of the matrix metalloproteinase gene family, could be expressed to dissolve the extracellular matrix components. Fouad et al [15] revealed that MMP-9 was significantly up-regulated in both blood and urine of BCa patients and was of great discriminatory ability in the diagnosis of BCa. Wong et al [16] also demonstrated that MMP9 was a potential therapeutic target and prognostic biomarker that contribute to the progression of BCa.…”
Section: Discussionmentioning
confidence: 99%
“…Deregulated MMP-9 expression and/or activity causes cellular invasiveness and leads to the growth and clinical progression of a wide variety of human cancers [ 10 , 14 , 15 , 16 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Mmp-9 Production or Activity Is Regulated At Multiple Levmentioning
confidence: 99%
“…The role that MMP-9 has in the development of the primary tumor has been described elsewhere [ 14 , 15 , 16 ]. Herein, the available scientific literature concerning the impact that the deregulated expression or activity of MMP-9 might exert on solid tumor metastases is reviewed in the context of a Special Issue of the International Journal of Molecular Sciences, entitled “Tumor Cell Invasion and Metastases”.…”
Section: Introductionmentioning
confidence: 99%
“…First, we performed in vitro experi- variety of human cancers, including BC. [25][26][27][28][29] We therefore predicted that these proteins may be useful markers to monitor biological behaviours of BC cells in SNHG1-mediated modulation. Collectively, these results revealed that SNHG1 is capable of promoting BC progression by facilitating BC cell proliferation, migration, invasion and EMT.…”
Section: Snhg1 Promotes the Proliferation Migration And Invasion Omentioning
confidence: 99%